Paul Tillich on Art. Issue 1 (January 2016) - Truss, Richard
Abstract : For Tillich, theology and art are mutually illuminating and 'all art is religious'. He relates particular artistic styles directly to types of religious experience. A problem for Tillich is matching the sometimes fragmentary nature of art to his essentially unifying idea of Being-itself.